Hubungan Antara Kontrol Diri Dengan Kecenderungan Agresivitas Pada Remaja Di SMK Negeri 3 Yogyakarta - Tarigan, Meirida Aulina; , Setia Asyanti, S.Psi., M.Si (2016)
Aggression phenomenon done by adolescence individual or simultaneously such as an brawl and get fight that become a news on news paper or electric media become a background of this research. Adolescences should study and prepare their selves for their future instead do on the tendency of aggression. Aggression tendency is an action to hurt others physically or verbally. It is influence by many factors, such as self control. The purpose of this research to know the relation between self control and aggression tendency in adolence. This research was held at SMK Negeri 3 Yogyakarta. The participants are adolences who study at XI grade in SMK Negeri 3 Yogyakarta, were 135 students who 16-18 years old. It wed Proportionate Random Sampling technique. This method used in this research is quantitative with the measurement such as a scale, they are the aggression tendency and self control scale, an opened quesioner. The technique analysis of data is used the correlation of Product Moment by Pearson. Based on the analysis result shown the value of correlation coefisience r= 0,979; p= 0,000 (p<0,01) it means there are the significant relathionship between self control and aggression tendency. The variable of aggression tendency is include to medium category. While the variabel of self control is high category. The result of quesioner shows that the frequency and percentage of aggression tendency on student is less.